The Impact of Information and Technology in Education - Intan Permatasari; Dayat Hidayat; Yousef ad Bani Ahmad (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
Learning technology continues to develop along with the times. In the implementation of daily learning, we often encounter the use of information and technology developments in the world of education, as is often done by teachers or lecturers, namely combining information and technology tools in the learning process. However, information and technology will not only bring positive benefits, but will also have a negative impact. The development of information science and technology has a positive impact by increasing the openness and dissemination of information and knowledge from and to all over the world across the boundaries of space and time. The negative impact is the occurrence of changes in behavior, ethics, norms, rules, or morals of life that are contrary to the ethics, norms, rules, and morals of life that exist in society.